O desafio de ser e de atuar como docente universitário - Osvaldo Dalberio; Ailton Paulo de Oliveira Júnior (EccoS – Revista Científica)
This paper presents a discussion of the narrative of the teaching practice of three teachers who teach their classes in a higher education institution in the city of Uberaba, in the Minas Gerais State, with different academic experiences. We answer our concerns about the challenges of being a university professor and discuss the educational role of teaching and teacher whose accountability in higher education is to prepare the student to perform a social function. We believe that the teacher promotes alternatives at time of the acquisition of knowledge or performing tasks of teaching, of research and of the extension. Thus, the role of the university professor is an ongoing challenge.